Thermoelectric characteristics of textured KSr2Nb5O15 ceramics. (February 2016) - Duran, Cihangir; Yildiz, Abdullah; Dursun, Sinan; Mackey, Jon; Sehirlioglu, Alp
Abstract: Effect of crystal anisotropy on thermoelectric properties of textured KSr2 Nb5 O15 ferroelectric ceramics is studied for the first time. Temperature dependent conductivity and Seebeck coefficient were measured in directions parallel and perpendicular to the c direction. A transition in electrical conduction from semiconductor to metallic behavior was observed at around 610 K. The power factor was remarkably improved depending on measurement directions such that it was 390 μW/mK 2 in parallel and 283 μW/mK 2 in perpendicular to the c direction at 1120 K. Textured KSr2 Nb5 O15 ceramics are promising candidates to be used as n-type thermoelectric materials at high temperatures and oxidizing environments. Graphical abstract: